El Sentido Que Tiene El Deporte Formativo En Los Estudiantes Del Programa De Enfermería De La Universidad Del Quindío (2014)
Qualitative research project of comprehensive approach. Carried out between 2013 and 2014 in the city of Armenia, Quindío (Colombia), by Antony Tabima and Julian Andrés Oviedo, students of the Physical Education and Sports Degree Program of the University Quindío. Its general objective is to understand the meaning that the formative sport has on students of the Nursing Program at the University of Quindío. It is supported on the vision of sense that Berger and Luckman have from the theoretical point of view. Methodologically speaking, this research can be framed within the ethnographic and quasi-ethnographic research; therefore it employed as research tools the direct observation, field notes, semi-structured interviews and in-depth interviews. People whom it was worked with are students of the Nursing Program at the University of Quindío who allowed, thanks to the provided information, to obtain five categories that are included in the results, these are: I. About the formative sport II. Formative sport compulsory III. Importance of formative sport IV. Formative sport and Nursing: a good duo V. The class: a contribution to nurses or teaching for life. KEY WORDS: formative sport, nursing, sense, University of Quindío, universitary sport, physical education, life healthy habits, physical activity.